2016
DOI: 10.1016/j.aprim.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Fiabilidad de los registros electrónicos de prescripción de medicamentos de Atención Primaria

Abstract: Primary Care computerised medication records, although of undoubted interest, are not be reliable enough to be used as the sole source of information on patient chronic medications when admitted to hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
2
5
1
Order By: Relevance
“…In a veterans hospital in the USA, Kaboli et al found discrepancies between the CMPs analysed and the medication actually taken by the patients in 94.7% of cases 3. Consistent with these results, in a study conducted in a general hospital in Spain, García et al detected discrepancies in 97.1% of the CMPs analysed 4. Also in line with these studies, a multicentre study by Price et al in Canada showed discrepancies in 84% of cases,5 a study by Uitvlugt et al 7 in the Netherlands showed discrepancies in 83% of cases and two studies by Bülow et al 8 9 involving Danish polypharmacy patients showed discrepancies in 75% and 88% of cases, respectively.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…In a veterans hospital in the USA, Kaboli et al found discrepancies between the CMPs analysed and the medication actually taken by the patients in 94.7% of cases 3. Consistent with these results, in a study conducted in a general hospital in Spain, García et al detected discrepancies in 97.1% of the CMPs analysed 4. Also in line with these studies, a multicentre study by Price et al in Canada showed discrepancies in 84% of cases,5 a study by Uitvlugt et al 7 in the Netherlands showed discrepancies in 83% of cases and two studies by Bülow et al 8 9 involving Danish polypharmacy patients showed discrepancies in 75% and 88% of cases, respectively.…”
Section: Introductionsupporting
confidence: 56%
“…In the study published by García-Molina et al 4 in which 308 patients admitted to a cardiology-pneumology unit of a hospital in Murcia (Spain) were enrolled, the authors found that, in 97.1% of cases, CMPs had some kind of discrepancy. The difference in the rate of discrepancies compared with our study may result from the fact that restricted prescription drugs (HO, HD) could not be prescribed through the electronic prescribing platform used in their study, in contrast with RELE which admits this type of drugs, and this may have generated more discrepancies with the medication actually taken by patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations